High Dose Vitamin D3 Supplementation Is Not Associated With Lower Mortality in Critically Ill Patients: A Meta-Analysis of Randomized Control Trials - Gao, Zhiwei; Xie, Jianfeng; Li, Cong; Liu, Ling; Yang, Yi (Frontiers in Nutrition, 2022)
Background Vitamin D deficiency is a common condition in critically ill patients. A high dose of vitamin D3 can rapidly restore vitamin D levels. The aim of this meta-analysis was to synthesize the results from up-to-date randomized control trials (RCT) and validate the effect of vitamin D3 in critically ill patients. Study Methods Several databases, including PubMed, Web of Science, EMBASE, and the Cochrane Central database, were searched up to December 4th, 2020. All RCTs that investigated the use of a high dose of vitamin D3 in critically ill patients and reported mortality data were included in the meta-analysis. The primary outcome was the mortality truncated to day 28 and day 90. Results A total of 10 RCTs enrolling 2058 patients were finally included. The use of a high dose of vitamin D3 in critically ill patients could not decrease the mortality truncated to day 28 (RR 0.93, 95% CI 0.78–1.11, P = 0.43) or day 90 (RR 0.91, 95% CI 0.79–1.05, P = 0.21). A high dose of vitamin D3 could significantly reduce the ventilator days (MD −9.38, 95%CI −13.44 to −5.31, P < 0.001), but there were no statistic difference in length of ICU stay (MD −2.76, 95% CI −6.27 to 0.74, P = 0.12) and hospital stay (MD −2.42, 95% CI −6.21 to 1.36, P = 0.21). No significant difference was observed in adverse events between the vitamin D3 group and the placebo group. Conclusion The use of high dose vitamin D3 was not associated with decreased mortality in critically ill patients, but could significantly reduce the ventilator days. Systematic Review Registration https://www.crd.york.ac.uk/prospero/, identifier: CRD42020179195.